M5-branes wrapped on four-dimensional orbifolds - Sparks, JF; Gauntlett, J; Fry, J; Cheung, M (Springer, 2022)
We construct supersymmetric AdS3 solutions of D = 11 supergravity, dual to d = 2, N = (0, 2) SCFTs, that are associated with M5-branes wrapping two different four-dimensional orbifolds. In one case the orbifold is a spindle fibred over another spindle, while in the other it is a spindle fibred over a Riemann surface with genus g > 1. We show that the central charges of the d = 2 SCFTs calculated from the gravity solutions agree with field theory computations using anomaly polynomials. The new D = 11 solutions are obtained after constructing a new consistent Kaluza-Klein truncation of maximal D = 7 gauged supergravity reduced on a spindle down to D = 5 minimal gauged supergravity.